Biallelic inactivation of the NF1 tumour suppressor gene in juvenile myelomonocytic leukaemia: Genetic evidence of driver function and implications for diagnostic workup - Ramamoorthy, Senthilkumar; Lebrecht, Dirk; Schanze, Denny; Schanze, Ina; Wieland, Ilse; Andrieux, Geoffroy; Metzger, Patrick; Hess, Maria; Albert, Michael H; Borkhardt, Arndt; Bresters, Dorine; Buechner, Jochen; et al. (British journal of haematology, 2024)
Juvenile myelomonocytic leukaemia (JMML) is characterized by gene variants that deregulate the RAS signalling pathway. Children with neurofibromatosis type 1 (NF-1) carry a defective NF1 allele in the germline and are predisposed to JMML, which presumably requires somatic inactivation of the NF1 wild-type allele. Here we examined the two-hit concept in leukaemic cells of 25 patients with JMML and NF-1. Ten patients with JMML/NF-1 exhibited a NF1 loss-of-function variant in combination with uniparental disomy of the 17q arm. Five had NF1 microdeletions combined with a pathogenic NF1 variant and nine carried two compound-heterozygous NF1 variants. We also examined 16 patients without clinical signs of NF-1 and no variation in the JMML-associated driver genes PTPN11, KRAS, NRAS or CBL (JMML-5neg) and identified eight patients with NF1 variants. Three patients had microdeletions combined with hemizygous NF1 variants, three had compound-heterozygous NF1 variants and two had heterozygous NF1 variants. In addition, we found a high incidence of secondary ASXL1 and/or SETBP1 variants in both groups. We conclude that the clinical diagnosis of JMML/NF-1 reliably indicates a NF1-driven JMML subtype, and that careful NF1 analysis should be included in the genetic workup of JMML even in the absence of clinical evidence of NF-1.
Keywords: mutace; juvenilní myelomonocytární leukemie; Signal Transduction; tumor supresorové geny; Child; lidé; Genes, Tumor Suppressor; dítě; Mutation; neurofibromatóza 1; signální transdukce; Neurofibromatosis 1; Leukemia, Myelomonocytic, Juvenile; Humans